Workplace Conflict On Productivity and Emotional Stability of Employee - Joseph Kayode Adeyemi (International Journal of Management and Business Applied, 2022)
Abstract Some recent observers noticed that employee productivity nearly on all kind of organizations is diminishing on a day-to-day basis, particularly in the field of education. The researcher found a number of factors that affected the productivity of employees. One of the major factor contributing to the productivity of employees is workplace conflicts. Therefore, the main goal of this study was to examine the workplace conflicts and its effect on the employee productivity and emotional stability. This research also examined a mediating role of workplace politics between the workplace conflicts and employee productivity among the members of the faculty of education Adekunle Ajasin university, Akungba-Akoko, Ondo State, Nigeria. Stratified sampling technique was used to collect the data from concerned population by using structured questionnaire. To achieve the goals of study different statistical techniques were used by using SPSS. Reliability test was used to check the data reliability. Furthermore, t-test analysis was used to investigate the relationship between workplace conflicts and employee productivity. The finding of this test showed that the relationship between workplace conflicts and employee productivity is negative. Macro process tool was used to investigate that whether workplace politics mediates the relationship between workplace conflicts and employee productivity. The finding of this test showed that workplace conflicts significantly predict emotional stability of employee and employee productivity.